2014
DOI: 10.1007/s13187-014-0646-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Colorectal Cancer Screening in Vietnamese Americans: A Qualitative Analysis

Abstract: Background Vietnamese Americans are the fourth largest Asian ethnic group in the United States. Colorectal cancer (CRC) ranks as one of the most common cancers in Vietnamese Americans. However, CRC screening rates remain low among Vietnamese Americans, with 40% of women and 60% of men reporting never having a sigmoidoscopy, colonoscopy, or Fecal Occult Blood Test. Methods We partnered with a Federally Qualified Health Center (FQHC) in Seattle, Washington, to conduct focus groups as part of a process evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 40 publications
2
44
0
2
Order By: Relevance
“…Despite potential facilitators, such as receiving mailings in their preferred language and wordless instructions, most of those who received the FIT kits did not complete the screenings. Prior studies have identified several potential barriers, including fear about what the test may indicate, the cost of follow‐up colonoscopy, the potential risk of perforation, embarrassment of a fecal collection procedure, concerns about mailing fecal matter, and being busy or forgetful . Future efforts to improve the uptake of CRC screening in MailedFIT programs should address these concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite potential facilitators, such as receiving mailings in their preferred language and wordless instructions, most of those who received the FIT kits did not complete the screenings. Prior studies have identified several potential barriers, including fear about what the test may indicate, the cost of follow‐up colonoscopy, the potential risk of perforation, embarrassment of a fecal collection procedure, concerns about mailing fecal matter, and being busy or forgetful . Future efforts to improve the uptake of CRC screening in MailedFIT programs should address these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified several potential barriers, including fear about what the test may indicate, the cost of follow-up colonoscopy, the potential risk of perforation, embarrassment of a fecal collection procedure, concerns about mailing fecal matter, and being busy or forgetful. [18][19][20][21] Future efforts to improve the uptake of CRC screening in MailedFIT programs should address these concerns. The variation we observed in the FIT kit return rate by patient language should be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…At the interpersonal level, lack of social support has also been reported as a barrier to CRC screening participation (30). Finally, at the individual level, previously reported barriers include lack of knowledge about detection and disease (22,(31)(32)(33)(34), underestimation of CRC risk(35, 36), procrastination(37), fear of a cancer diagnosis (21,28,34,(37)(38)(39), fear of discomfort or pain during colonoscopy (34,40,41), and shame about getting a colonoscopy (34,40,41). Our study participants perceived as hypothetical facilitators the removal of financial barriers and implementation of educational interventions for patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…At the interpersonal level, lack of social support has also been reported as a barrier to CRC screening participation (30). Finally, at the individual level, previously reported barriers include lack of knowledge about detection and disease (22,(31)(32)(33)(34), underestimation of CRC risk (35,36), procrastination (37), fear of a cancer diagnosis (21,28,34,(37)(38)(39), fear of discomfort or pain during colonoscopy (34,40,41), and shame about getting a colonoscopy (34,40,41). Our study participants perceived as hypothetical facilitators the removal of financial barriers and implementation of educational interventions for patients and providers.…”
Section: Discussion 13mentioning
confidence: 99%